The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3389/fpsyt.2018.00329
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Brain Abnormalities Associated With Exposure to Different Childhood Trauma Subtypes: A Systematic Review of Neuroimaging Findings

Abstract: Background: Childhood trauma subtypes sexual abuse, physical abuse, emotional maltreatment, and neglect may have differential effects on the brain that persist into adulthood. A systematic review of neuroimaging findings supporting these differential effects is as yet lacking.Objectives: The present systematic review aims to summarize the findings of controlled neuroimaging trials regarding long-term differential effects of trauma subtypes on the human brain.Methods: A systematic literature search was performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
101
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(123 citation statements)
references
References 95 publications
17
101
1
4
Order By: Relevance
“…As mentioned previously, qualitatively different types of traumas can produce distinct neurobiological and behavioral consequences (e.g., Ref. 21 ). In addition, while the DSM uses a binary approach to define the boundary between “stress” and “trauma,” it may be important to focus more on qualitative aspects of distinct types of intense stressors and less on a dichotomous variable.…”
Section: Preclinical Models Of Traumatic Stress Exposurementioning
confidence: 80%
See 1 more Smart Citation
“…As mentioned previously, qualitatively different types of traumas can produce distinct neurobiological and behavioral consequences (e.g., Ref. 21 ). In addition, while the DSM uses a binary approach to define the boundary between “stress” and “trauma,” it may be important to focus more on qualitative aspects of distinct types of intense stressors and less on a dichotomous variable.…”
Section: Preclinical Models Of Traumatic Stress Exposurementioning
confidence: 80%
“…Some individuals experience rapid and sustained natural recovery, while others develop chronic trauma-related psychopathology 3 . Importantly, the nature and extent of trauma exposure combine to produce different outcomes; research suggests that exposure to qualitatively different events and different degrees of exposure lead to different psychiatric and neurobiological outcomes 4 21 . For example, qualitatively different events (e.g., rape, assault, and natural disaster) are associated with different levels of conditional risk for posttraumatic stress disorder (PTSD; 19% rape and 0.3% natural disaster) 20 .…”
Section: Introductionmentioning
confidence: 99%
“…Additional research has shown ELT negatively impacts brain function, with increased functional connectivity and activation in limbic structures during an emotional processing task ( Jedd et al, 2015 ) as well as a sustained attention task ( Fortenbaugh et al, 2017 ) and decreased functional connectivity between amygdalae and prefrontal regions at rest ( Fan et al, 2014 , Pagliaccio et al, 2015 ). Moreover, a recent meta -analysis reported structural and functional abnormalities in association with childhood trauma type ( Cassiers et al, 2018 ), further implicating disruptions to both structure and function in association with ELT.…”
Section: Introductionmentioning
confidence: 99%
“…Dimensional approaches have increasingly focused on key aspects of early adversity (Cicchetti & Toth, 1995;Cohodes et al, 2020;Everaerd et al, 2016;McCoy, 2013;McLaughlin et al, 2014;Pynoos et al, 1999), including the type of adversity experienced (Dennison et al, 2019;Machlin et al, 2019;McLaughlin et al, 2014;Miller et al, 2018;Sheridan et al, 2017). Previous work directly comparing distinct types of exposures (e.g., physical abuse, sexual abuse, physical neglect, emotional neglect) has demonstrated differential impacts on brain structure (Cassiers et al, 2018;Edmiston et al, 2011;Heim et al, 2013;Tomoda et al, 2009Tomoda et al, , 2012van Harmelen et al, 2010). Examining findings across studies of specific types of adversity has also suggested unique associations with brain structure.…”
Section: Introductionmentioning
confidence: 99%